ln(5-x)=e

Simple and best practice solution for ln(5-x)=e equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(5-x)=e equation:


Simplifying
ln(5 + -1x) = e
(5 * ln + -1x * ln) = e
(5ln + -1lnx) = e

Solving
5ln + -1lnx = e

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-1e + 5ln + -1lnx = e + -1e

Combine like terms: e + -1e = 0
-1e + 5ln + -1lnx = 0

The solution to this equation could not be determined.

See similar equations:

| x^8=108 | | f(x)=0.3+x | | -5(1-2x)=25+5x | | -16+5x=-7+4(x-3) | | 7.3=77-(-2)(6x+25)+8(75x-1) | | 6(n+6)+2n=8n+43 | | 4dx^3-2dy+6dx-by=0 | | -36+6v=-6(5-v)-6 | | -36+6v=6(5-v)-6 | | 9v+9=90 | | 8x-4=2+-7x | | 8-b=3(b+7)+7 | | 13x-3=-10 | | -7.5x+0.37=-2.63 | | 3(-5-6)+2=-28-3n | | -5-3k=22 | | 4x-37=956 | | 9+2x=2x | | 4(x+7)=33+4x | | 6(9s-4)=24-8s | | (5x+2)-3=3x-8+7 | | -30+6r=-4(6-2r) | | 4(3a+8)+7a=-a+32 | | -8(x+8)=-56 | | 9a+8+6=-20 | | -(x+2)-7=-37+6x | | 33=4y+5y | | Tan^2x-2tanx=1 | | 9(1+2r)=30 | | 5h-6h=-17 | | (2x-5)+(x+40)+64=180 | | -9+3y=3 |

Equations solver categories